2020
DOI: 10.1371/journal.pmed.1003140
|View full text |Cite
|
Sign up to set email alerts
|

The association between use of proton-pump inhibitors and excess mortality after kidney transplantation: A cohort study

Abstract: Background Chronic use of proton-pump inhibitors (PPIs) is common in kidney transplant recipients (KTRs). However, concerns are emerging about the potential long-term complications of PPI therapy. We aimed to investigate whether PPI use is associated with excess mortality risk in KTRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Xie and colleagues showed a small excess of cause specific mortality due to cardiovascular disease, chronic kidney, disease, and upper gastrointestinal cancer in patients taking PPIs [25]. In addition, another cohort study determined increased risk of overall mortality with PPI use in kidney transplant recipients with average eGFR of 52 [26]. These findings are in contrast with the results from Grant's study which looked at the CKD population specifically and found no association between PPI use and increased mortality.…”
Section: Discussionmentioning
confidence: 90%
“…Xie and colleagues showed a small excess of cause specific mortality due to cardiovascular disease, chronic kidney, disease, and upper gastrointestinal cancer in patients taking PPIs [25]. In addition, another cohort study determined increased risk of overall mortality with PPI use in kidney transplant recipients with average eGFR of 52 [26]. These findings are in contrast with the results from Grant's study which looked at the CKD population specifically and found no association between PPI use and increased mortality.…”
Section: Discussionmentioning
confidence: 90%
“…The comparable rates of mortality and graft loss are other important points to be considered. Higher rate of mortality was reported in PPIs‐treated patients among transplant and non‐transplant population in some studies 25,28,29 ; therefore, this result should be interpreted with caution and should be evaluated in further studies with a higher population number. PPIs use is associated with development of acute and chronic kidney damage with several mechanisms such as recurrent acute interstitial nephritis or endothelial dysfunction 8 …”
Section: Discussionmentioning
confidence: 76%
“…Our updated meta‐analysis of PPIs versus H2RAs confirmed these results. One large cohort study demonstrated that PPIs use is associated with a dose‐dependent, increased mortality risk in KTRs independent of potential confounders compared with non‐PPIs users 29 ; however, that study did not mention the rate of H2RAs users among patients in non‐PPIs user group. Other potential short‐ and long‐term adverse effects of the acid‐suppressive therapies, especially PPIs, are fracture risk, 4,8 hypomagnesemia 23,31 and risk of Clostridioides difficile infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is, however, not standard policy in transplant centers worldwide, probably because of an absence of scientific data and guideline recommendation that support the routine use of PPIs post‐transplant. Added to this, previous studies performed among chronic kidney disease (CKD) populations and transplant populations show that PPI use is associated with a higher risk of hypomagnesaemia, acute kidney injury, incident CKD, CKD progression and even premature mortality [ 27 , 28 ]. Although the evidence for these adverse effects mainly comes from observational studies, it does emphasize the need to avoid unnecessary use of PPIs after transplantation.…”
Section: Discussionmentioning
confidence: 99%